(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article highlights the didactic features of the spiritual significance of the Alpomish epic as well as its role today. Also, the Uzbek folk epic is a scientific, artistic version of the Alpomish epic the significance, mythological motifs in the saga, and the characters ’ heroics are covered. The epic of Alpomish is expressed as a whole of national values.